Augmented Reality Integration in Quran Learning: Innovation of Tahsin and Tahfidz Methods for Amir Hamzah Medan Junior High School Students - Hasibuan, Marhan; Hidayat, Muhammad Arif (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
The integration of AR aims to create a learning experience that is more interesting, interactive and easy to understand so that students are more focused, motivated and actively involved in learning and memorising the Quran. and actively involved in learning and memorising the holy verses of the Quran. Method methods used in this community service activity are socialisation methods, training teachers and students, AR-based learning implementation, mentoring and monitoring. AR-based learning implementation, mentoring and monitoring. The results obtained are an increase in students' tahsin and tahfidz skills, increased student interest and enthusiasm in learning the Quran, increased digital literacy of students and teachers. in learning the Koran, increasing digital literacy of students and teachers. Conclusion from This service activity is the integration of Augmented Reality (AR) in learning the AL-Quran at Amir Hamzah Medan Junior High School is proven to be effective in improving students' tahsin and tahfidz students.